The superiority of Zymomonas mobilis in producing bioethanol from Coffea arabica peel using cellulolytic enzyme treatment - Widyaningrum, Trianik; Utami, Listiatie Budi (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
As petroleum supplies are being depleted, there is a growing need for bioethanol as an alternative energy source. With the aid of crude cellulose enzymes from Bacillus subtilis IFO 13719, coffee arabica peels can be used as one of the waste materials to manufacture bioethanol. Microorganisms that can convert sugar into bioethanol, specifically Saccharomyces cerevisiae and Zymomonas mobilis, are also necessary for the synthesis of bioethanol. The purpose of this study is to demonstrate Zymomonas mobilis's superiority in generating bioethanol from fermented Arabica coffee peels treated with the crude cellulose enzyme B. subtilis. The concentrations of the B. subtilis crude cellulase enzyme at 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15%, and 17.5% were all independent variables in the fully randomized experimental design. The amount of sugar and ethanol is the dependent variable. The DNS method was used to measure the sugar concentration, and an alcohol meter was used to determine the ethanol content. Data analysis using the SPSS 16 software to examine DMRT and one-way ANOVA. The results showed that the maximum sugar content (1.0 g/mL) was obtained with the cellulase enzyme B.subtilis 2.5 % and the highest ethanol content (4.46 %) was obtained with the crude enzyme B. subtilis concentration 10% and fermented using Z. mobilis.